Utility of the triglycerides/HDL-C index from the first years of age in the diagnosis of metabolic syndrome in obese children - Cabello, Emilio (2020)
Objective: To determine the utility of the triglycerides/HDL-C index for the diagnosis of metabolic syndrome (MS) in obese 2-14 years of age children. Methods: Cross-sectional diagnostic study. We included 360 exogenous obese children (199M/161F) divided in three age groups: 2 to <6; 6 to <10 and 10-14 years. MS was defined according to the International Diabetes Federation and the TG/HDL-C index was evaluated using two cutoffs by age group, ≥2.32 and ≥3.5. Chi squared was used accepting a p value <0.05 as statistically significant. Fir each cut-off we determined sensitivity, specificity and predictive values. Results: Frequency of MS was 15.79% in the 2 to <6 years age group; 20.25% in the 6 to<10 years age group and 19.63% in the 10-14 years age group. Among children with SM, 97.1% had low HDL and 83.8% had elevated triglycerides. A statistically significant difference was found in the frequency of the TG/HDL-C index in children with or without MS in all age groups. Sensitivity for all cut-offs was high (86-100%) and specificity was best for the cut-off of ≥3.5 (72-80%). Conclusions: The TG/HDL-C index is a sensitive and specific marker of MS from the first years of age.